2006
DOI: 10.1111/j.1654-1103.2006.tb02440.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon—nutrient balance on herb and woody plant abundance in temperate forest understories

Abstract: Question: We present a general structural carbon—nutrient balance hypothesis parallel to Bryant et al.'s defensive chemistry hypothesis. Our hypothesis suggests that because herb species require a lower investment of carbon per unit length of stem than do woody plants, herbs should be at a competitive advantage where the leaf area of plants in the ground layer is limited by light (or fixed carbon, C) rather than soil resources (R) such as nutrients or water. We test the derivative predictions that in temperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…For instance, the negative correlation between pH and grass biomass was consistent with the suggestion made by Barnes et al (1991) that grass biomass is influenced by the increased level of soil pH. According to Graves et al (2006), herbaceous species were abundant under improved soil conditions suggesting that soil conservation is crucial for the restoration of herbaceous species richness and diversity. In contrast, increased grass biomass under high silt-clay particles could be an indicator of the positive relationship between organic carbon and silt-clay particles.…”
Section: Relationships Between Soil Characteristics and Vegetation Vasupporting
confidence: 83%
See 2 more Smart Citations
“…For instance, the negative correlation between pH and grass biomass was consistent with the suggestion made by Barnes et al (1991) that grass biomass is influenced by the increased level of soil pH. According to Graves et al (2006), herbaceous species were abundant under improved soil conditions suggesting that soil conservation is crucial for the restoration of herbaceous species richness and diversity. In contrast, increased grass biomass under high silt-clay particles could be an indicator of the positive relationship between organic carbon and silt-clay particles.…”
Section: Relationships Between Soil Characteristics and Vegetation Vasupporting
confidence: 83%
“…Generally, our results show that soil pH, EC, CEC, CaCO 3 and certain nutrients (i.e., K þ , Ca 2þ , Mg 2þ , N, OC and P) promote the invasion of bush encroachment. Essentially, results from a concurrent study indicate that some soil characteristics may trigger the spread of bush encroachment (Graves et al, 2006). According to Jackson et al (2002), processes such as an increase in soil carbon content can cause the invasion of bush encroachment under low rainfall conditions.…”
Section: Relationships Between Soil Characteristics and Vegetation Vamentioning
confidence: 97%
See 1 more Smart Citation
“…Secondary succession studies conducted across the EDF show a clear contrast of seral herbaceous communities across regions: in the Northeast, rapid colonization by clonal, fast-growing herbs such as Solidago altissima is typical except on very coarse soils, whereas southern old fields are more typically dominated by perennial bunchgrasses such as Andropogon virginicus (Wright and Fridley 2010), a species widely believed to be tolerant of drought and nutrient stress (Bazzaz 1968). At the same time, soils of lower C to nutrient ratios may stoichiometrically favor herbs in competition with woody seedlings of higher tissue C to nutrient Table 4 ratios (Larcher 2001;Sterner and Elser 2002;Graves et al 2006); furthermore, the greater evaporative demands and lower water retention capacity of coarser southern soils may limit the apical growth of species with herbaceous stems via turgor loss. Although our experiment was not designed to differentiate between direct effects of soil properties on seedling growth versus indirect effects of herbaceous competitors, we were able to compare the effects of a general axis of site fertility to that of climate, and soils were a stronger predictor of seedling performance.…”
Section: Discussionmentioning
confidence: 98%
“…However, here again additional analyses utilizing slope and aspect (not shown) indicated that these variables also only contributed a small fraction of explained variance. Moisture and nutrient availability are also known to shape herbaceous understory community composition (Ludwig et al 2004;Galhidy et al 2006;Graves et al 2006), but we did not collect information on either of these variables. There are many other potential biological drivers of community structure in our study system which include, but are not limited to, Janzen-Connell effects, herbivory, competitive exclusion, dispersal limitation, variation in growth forms, extent of rooting zone, and patterns of vegetative reproduction.…”
Section: Habitat Differencesmentioning
confidence: 99%